Medical Ethics and Health Equity: The Henrietta Lacks Story - Lisa Barkley; Deleso Alford (MedEdPORTAL, 2015)
Abstract Introduction With the increasing of diversity in the U.S. and globally, it is imperative that medical students have sound foundational knowledge of the principles of health equity. This team-based learning (TBL) module is part of our Psychosocial Issues in Healthcare course for first-year medical students, and serves as a learning module for the University of Central Florida College of Medicine longitudinal curricular thread in Culture, Health, and Society. This course is designed to prepare first-year medical students to address key issues that impact the provision of healthcare and the doctor-patient relationship. The TBL format allows for qualitative and quantitative means to assess student learning outcomes and promote higher level learning on Bloom's taxonomy with critical analysis on how to address healthcare disparities and promote health equity. Methods Students arrived at the session having reviewed pre-assigned readings. They then took an individualized readiness assurance test (IRAT), before breaking into preassigned teams and taking a group readiness assurance test (GRAT). In groups they then completed a series of application-focused exercises (AFEs) designed to make teams apply the concepts from the learning objectives and the assigned readings to clinical scenarios. Finally, an individual reflection exercise was completed to ensure that students understood and could personalize the concepts that were introduced in the learning module. Results This TBL was implemented in 2014 and in 2015. The mean IRAT score in 2014 was 86.3%, with a standard deviation of 12.2%. The mean GRAT score was 98.9%. The mean AFE score was 99%. The IRAT was revised, and in 2015, the median IRAT score was 75% (SD = 1.22). The AFE was not graded in the second year as multiple responses can be correct and we wanted the students to share their different perspectives. The mean GRAT score was 96.3%. The increase in the GRAT score from the IRAT score demonstrates that student learning was occurring in the group discussions. Discussion Faculty who adopt this TBL should be comfortable discussing race, gender, social class and other social constructs that promote inequity in our society. It is important to foster an atmosphere where students feel comfortable expressing their feelings by welcoming and affirming all perspectives. Our experience is that students want to have discussions on these often-difficult and traditionally marginalized realities that ultimately impact effective health care delivery.